2005
DOI: 10.1007/s11104-004-1523-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, biomass and nutrient status of fine roots of Scots pine (Pinus sylvestris) as influenced by seasonal fluctuations in soil moisture and soil solution chemistry

Abstract: A field monitoring study was carried out to follow the changes of fine root morphology, biomass and nutrient status in relation to seasonal changes in soil solution chemistry and moisture regime in a mature Scots pine stand on acid soil. Seasonal and yearly fluctuations in soil moisture and soil solution chemistry have been observed. Changes in soil moisture accounted for some of the changes in the soil solution chemistry. The results showed that when natural acidification in the soil occurs with low pH (3.5-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 20 publications
4
44
0
Order By: Relevance
“…In particular, a higher necromass is attributed to the fact that fine root systems on acidic and poor sites have a higher mortality rate (Leuschner et al 2004). In addition, fine roots from soils with a low BS may have a decreased longevity due to nutrient deficiencies (low BS) and/or Al 3+ toxicity, as observed by Vanguelova et al (2005) in a Scots pine stand. Nevertheless, Gaudinski et al (2001) showed an increase in the age of fine roots measured by radiocarbon with increasing depth (4-6 years at 0-15 cm depth and 15-18 years at 15-30 cm depth), which may also explain the increased live/dead ratio with increasing depth.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In particular, a higher necromass is attributed to the fact that fine root systems on acidic and poor sites have a higher mortality rate (Leuschner et al 2004). In addition, fine roots from soils with a low BS may have a decreased longevity due to nutrient deficiencies (low BS) and/or Al 3+ toxicity, as observed by Vanguelova et al (2005) in a Scots pine stand. Nevertheless, Gaudinski et al (2001) showed an increase in the age of fine roots measured by radiocarbon with increasing depth (4-6 years at 0-15 cm depth and 15-18 years at 15-30 cm depth), which may also explain the increased live/dead ratio with increasing depth.…”
Section: Discussionmentioning
confidence: 97%
“…Commonly used fine root properties to assess the 'vitality' of the fine roots are the amount of biomass, necromass, and live/dead ratio, as well as the productivity and mortality of the fine roots. It has often been reported that forests growing on acidic sites have a higher fine root density and fine root mass of both bio-and necromass than forests growing on less acidic sites (Godbold et al 2003;Jentschke et al 2001;Vanguelova et al 2005). In particular, a higher necromass is attributed to the fact that fine root systems on acidic and poor sites have a higher mortality rate (Leuschner et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of rock phosphate as part of good forestry management practice (Taylor, 1991) may provide an additional buffer and therefore reduce managed woodland habitat sensitivity to acidification. In the long-term, continuing acidic inputs could result in reduced productivity on mineral soils as a result of aluminium toxicity (Vanguelova et al, 2004) or the development of nutrient imbalances or deficiencies, particularly of base cations. While there is some information on the potential impact of low pH on non-forest ecosystems developed on organic and peaty soils, the published evidence is less clear for woodlands developed on such soils.…”
Section: Discussionmentioning
confidence: 99%